Imaginaries of connectivity the creation of novel spaces of governance - Lobo-Guerrero, Luis; Alt, Suvi 1984-; Meijer, Maarten 1958- (Rowman & Littlefield International, Ltd, 2020)
"This edited collection addresses the problem of how the creation of novel spaces of governance relates to imaginaries of connectivity in time. While connectivity seems almost ubiquitous today, it has been imagined and practiced in various ways and to varying political effects in different historical and geographical contexts"--
Keywords: Geschichte 1500-2020; Governance; Entdeckung; Raum; Kommunikation; Vernetzung; Communication and geography / Case studies; Communication and culture / Case studies; Boundaries / Social aspects / Case studies; Boundaries / Social aspects; Communication and culture; Communication and geography; Case studies